(untitled) (American Journal of Medical Science and Innovation, 2024)
Varicocele is a condition causing abnormal dilatation of the pampiniform plexus in the scrotum, affecting spermatogenesis, testicular volume, semen parameters, fertilization, implantation, and embryonic outcomes. This systematic review and meta-analysis aimed to compare surgical and non-surgical management of Varicocele, evaluating fertility outcomes and complication rates, synthesizing clinical studies for effectiveness and safety. The methodology includes the systematic review of 26 studies and a meta-analysis of 16 studies, followed by the search strategy, data extraction, inclusion and exclusion criteria, data analysis, and data extraction strategy of the included selected studies. For the criteria of study selection, PRISMA chart has been created to review the selection process of included studies. Research indicates that undergoing surgery to cure varicocele enhances the likelihood of conception, sperm quality, live birth rates, and success of sperm retrieval. Varicocele embolization is one non-surgical treatment that provides rapid pain relief, minimum invasiveness, and a quicker recovery. Antioxidants can enhance sperm parameters and conception rates when combined with other treatments. Reproductive outcomes are improved by varicocele repair, which includes surgical and angiographic embolization. This procedure lowers sperm DNA fragmentation. For males with varicocele, surgery is still the major way to improve quality of life. It was concluded that Varicoceleectomy is the primary fertility treatment for men with varicocele, offering significant benefits in pregnancy rates, sperm parameters, and long-term results, while non-surgical approaches offer faster recovery and minimal invasiveness.